Repurposing 0.5% povidone iodine solution in otorhinolaryngology practice in Covid 19 pandemic - Khan, Mubarak Muhamed (Am J Otolaryngol, 2020)
SARS CoV 2 is very much homologous in structure to SARS CoV. Review of literature suggests the in-vitro virucidal action of povidone iodine in SARS CoV and MERS. The oropharynx and nasopharynx are target sites of SARS CoV 2. A significant proportion of COVID 19 sufferers are asymptomatic, but shedding these viral particles, PVP-I has been shown to be a safe therapy when used as a mouthwash or taken nasally or used during ophthalmic surgeries. AIMS: 1. To propose the use of 0.5% Povidone iodine gargles and nasal drops as prerequisite for office based nose and throat examination and procedures during COVID 19 pandemic. 2. To assess tolerability of 0.5% PVP-I in patients and in healthcare workers. MATERIALS AND METHODS: 0.5% PVP-I solution is prepared from commercially available 10% PVP-I solution. Patients were instructed to put 0.5% PVP-I drops in nose and rinse mouth with gargle prior examinations for 30 s. For endoscopic procedure (nasal and throat) nasal douching and gargling to be started one day prior. Douching and rinsing to be repeated just before procedures. Nasal packing with 0.5% PVP-I along with 4% xylocaine/adrenaline solution, tolerability and any allergic reaction noted. RESULTS: The patient and health care workers tolerated the 0.5%. No allergy was noted. CONCLUSION: We propose the use of 0.5% PVP-I in healthcare workers and their patients to minimise the risk of spread of the disease in addition to the recommended PPE.